The Design of A Motorcycle Featuring Fully Independent Adjustability for Front Suspension and Steering Geometry. Issue 1 (May 2019) - Gadola, Marco; Chindamo, Daniel; Vitale, Federico; Bonera, Emanuele
Abstract: The paper presents a feasibility study for a prototype motorbike (bike in short) with an alternative front suspension. Novel features include the adjustability of steering axis inclination, front trail, and anti-dive effect i.e. the main parameters affecting rider feedback and perception as well as motorcycle behaviour. Although being based on the well-known double-wishbone layout, the system can be adjusted to replicate the geometry of a conventional fork as a baseline for experimental testing. Unlike similar concepts that can be found in literature the kinematics can be modified by means of straightforward adjustments that do not require complex disassembly. Independent adjustability is provided for each parameter. These innovative features enable a back-to-back comparison between significantly different settings, in order to explore a wide range of characteristics in terms of dynamic response, handling properties and rider's perception with a single vehicle. The project is aimed at fostering knowledge on motorcycle dynamics within the research group and especially on rider feedback and subjective perception, somehow a neglected topic in current literature. It was undertaken under the form of a student educational project in mechanical engineering and named "F.A.B." (Fully Adjustable Bike). The paper is mainly focused on front suspension kinematics; chassis design and related structural aspects are outlined as well.